1998
DOI: 10.1007/s007050050439
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus hemagglutinin stimulates the protein kinase C activity of human polymorphonuclear leucocytes

Abstract: Human polymorphonuclear leukocytes (PMNL) incubated with influenza virus, A/USSR/90/77 (H1N1) or its hemagglutinin produced a significant increase in their PKC activity when compared with untreated PMNL. The activated kinase translocated from cytosol to cellular membrane. The calcium-dependent enzyme activity was inhibited by a specific inhibitor suggesting that alpha and/or beta isoforms of PKC were involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 10 publications
6
18
0
1
Order By: Relevance
“…As a validation of the approach, RPPA proteins were examined for changes of >25% in expression upon infection compared to levels previously reported in the literature (Table S3). As expected, several pathways were activated upon infection, including PKC, which is rapidly activated by influenza hemagglutinin 15 and is critical for enveloped virus entry;16, 17 ERK, which is upregulated by the influenza matrix protein 18 and is essential for viral RNP formation and nuclear export;19, 20 and nuclear factor κB (NF-κB), which has been shown to be crucial for IAV infection21, 22, 23 (Figure 2A, top). In addition, several markers that have previously been shown to be downregulated upon IAV infection were also suppressed in the RPPA study, including JAK124, 25, 26 and β-tubulin27, 28 (Figure 2A, bottom).
Figure 2Analysis of Changes in Global Pathway Signaling Molecules upon Infection or miRNA Transfection(A) Venn diagram of RPPA markers in untransfected cells whose levels were increased or decreased by >25% upon infection when compared to the uninfected average.
…”
Section: Resultssupporting
confidence: 58%
“…As a validation of the approach, RPPA proteins were examined for changes of >25% in expression upon infection compared to levels previously reported in the literature (Table S3). As expected, several pathways were activated upon infection, including PKC, which is rapidly activated by influenza hemagglutinin 15 and is critical for enveloped virus entry;16, 17 ERK, which is upregulated by the influenza matrix protein 18 and is essential for viral RNP formation and nuclear export;19, 20 and nuclear factor κB (NF-κB), which has been shown to be crucial for IAV infection21, 22, 23 (Figure 2A, top). In addition, several markers that have previously been shown to be downregulated upon IAV infection were also suppressed in the RPPA study, including JAK124, 25, 26 and β-tubulin27, 28 (Figure 2A, bottom).
Figure 2Analysis of Changes in Global Pathway Signaling Molecules upon Infection or miRNA Transfection(A) Venn diagram of RPPA markers in untransfected cells whose levels were increased or decreased by >25% upon infection when compared to the uninfected average.
…”
Section: Resultssupporting
confidence: 58%
“…This involves activation of Ca 2ϩ -dependent PKCs and Ras, respectively (47). It was shown before that influenza virus infection results in increased intracellular Ca 2ϩ concentration (51) and an increase in PKC activity in human polymorphonuclear leukocytes (52). Reduction of intracellular Ca 2ϩ concentration by EDTA was followed by decreased PKC activity, supporting the hypothesis that isoforms of Ca 2ϩ -dependent, conventional PKCs are activated during influenza virus infection (52).…”
Section: Ha-induced Signal Leading To Erk Activation Is Transmitted Vsupporting
confidence: 49%
“…It was shown before that influenza virus infection results in increased intracellular Ca 2ϩ concentration (51) and an increase in PKC activity in human polymorphonuclear leukocytes (52). Reduction of intracellular Ca 2ϩ concentration by EDTA was followed by decreased PKC activity, supporting the hypothesis that isoforms of Ca 2ϩ -dependent, conventional PKCs are activated during influenza virus infection (52). Furthermore, influenza virus entry seems to be dependent on PKC␤II but not on PKC␣ activity, indicating a role for PKCs early in infection (53).…”
Section: Ha-induced Signal Leading To Erk Activation Is Transmitted Vmentioning
confidence: 99%
“…PKC has also been shown to be critical for the entry of enveloped viruses (receptor-medicated endocytosis) [49]. Upon influenza virus infection, the hemagglutinin rapidly activates PKC [46,50] and it has been shown that a specific inhibitor of PKC prevents influenza virus replication by inhibiting the entry of the virus [51]. Similar results have also been reported in cells expressing a phosphorylation-deficient form of PKC [52].…”
Section: Protein Kinase C (Pkc) and Influenza Virus Entrysupporting
confidence: 73%